PENGARUH PRODUKSI, KONSUMSI PER KAPITA, HARGA DOMESTIK DAN HARGA INTERNASIONAL TERHADAP VOLUME IMPOR GULA INDONESIA - Prastika Sari, Ni Luh Indri; Sudirman, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
One of the food commodities that is needed by Indonesian people is sugar. The high domestic sugar consumption causes the government to import. However, excessive imports will cause domestic production to be less able to compete and damage market prices. This study aims to analyze whether there is a simultaneous, partial, and variable influence of the most dominant influence between production, consumption per capita, domestic prices and international prices on the volume of Indonesia's sugar imports in 2010-2017. To be able to solve the problem used multiple linear regression analysis techniques, F test for simultaneous influence, t test for partial effect and classical assumption test using eviews version 9 program. Simultaneously production, consumption per capita, domestic prices and international prices have a significant effect on the volume of Indonesia's sugar imports, while production is partially negative and significant, per capita consumption has a negative and significant effect, domestic prices have a positive and significant effect, lastly the domestic price has a negative and significant effect. keyword : sugar imports, production, per capita consumption, domestic price, international price